2013
DOI: 10.1002/jbm.a.34521
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of potential injectable polymeric biomaterials for bone regeneration

Abstract: This article reviews the potential injectable polymeric biomaterial scaffolds currently being investigated for application in bone tissue regeneration. Two types of injectable biomaterial scaffolds are focused in this review, including injectable microspheres and injectable gels. The injectable microspheres section covers several polymeric materials, including poly(l-lactide-co-glycolide)-PLGA, poly (propylene fumarate), and chitosan. The injectable gel section covers alginate gels, hyaluronan hydrogels, poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
85
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 97 publications
0
85
0
2
Order By: Relevance
“…Based on in vitro and in vivo studies, a low dose of BMP2 with a sustained release profile has been found optimal for osteogenesis [18][19][20]. Thus, there is a great need for a BMP2-encapsulated bone scaffold that is able to both retain the growth factor and preserve its bioactivity Materials Science and Engineering C 51 (2015) [16][17][18][19][20][21][22][23][24][25][26][27] for the duration necessary to attain conductive environment for osteogenesis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on in vitro and in vivo studies, a low dose of BMP2 with a sustained release profile has been found optimal for osteogenesis [18][19][20]. Thus, there is a great need for a BMP2-encapsulated bone scaffold that is able to both retain the growth factor and preserve its bioactivity Materials Science and Engineering C 51 (2015) [16][17][18][19][20][21][22][23][24][25][26][27] for the duration necessary to attain conductive environment for osteogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…HA nanoparticles encapsulated with BMP2 within the chitosan hydrogels [23] and PLGA/HA composite scaffolds [24] also enhanced the osteoinductivity of the respective materials. Despite promising results, the limitations noticed with such encapsulation techniques are initial burst release and decreased bioactivity of encapsulated proteins due to the organic solvents used in microsphere and nanoparticle fabrication [25,26]. Thus, growth factors subjected to harsh organic solvents during microsphere/scaffold synthesis were blended with bovine serum albumin (BSA) prior to encapsulation in order to provide a protective shell around the protein and subsequently preserving its bioactivity [17,27].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of injectable scaffolds compared to 3D porous scaffolds for orthopedic procedures is that they can be administered using 10-16-gauge needles at the bone defect site [17]. In addition, injectable scaffolds loaded with osteoinductive agents or therapeutic drugs minimize patient discomfort, scarring, operation time, and risk of infections from bone regeneration as a clinical treatment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymer microspheres as tissue engineering scaffolds have received increasing attention for their potential to regenerate and repair irregularly-shaped tissue defects due to their injectability, controllable biodegradability, and capacity of drug incorporation and release, making possible a clinical protocol that features minimal invasion and short-term manipulation in comparison to traditional surgical procedures [4, 5]. Biodegradable microspheres can be advantageous in repairing small irregularly-shaped dentin defects and allows for easier treatment of traditionally hard-to-reach dental defects.…”
Section: Introductionmentioning
confidence: 99%